2008
DOI: 10.5194/acp-8-5615-2008
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of UV irradiance within the area of one satellite pixel

Abstract: Abstract.A measurement campaign was performed in the region of Vienna and its surroundings from May to July 2007. Within the scope of this campaign erythemal UV was measured at six ground stations within a radius of 30 km. First, the homogeneity of the UV levels within the area of one satellite pixel was studied. Second, the ground UV was compared to ground UV retrieved by the ozone monitoring instrument (OMI) onboard the NASA EOS Aura Spacecraft. During clear-sky conditions the mean bias between erythemal UV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 19 publications
5
60
0
Order By: Relevance
“…For the specific campaign the number of days with variable or overcast cloud conditions was limited. Similar work of Weihs et al (2008) showed under partly cloudy conditions the satellite UV-values are, on average, in the order of 30% higher than the ground observations. The ratio OMI to ground UV becomes even larger for overcast conditions.…”
Section: Comparisons With Omi Overpass Datasupporting
confidence: 58%
See 3 more Smart Citations
“…For the specific campaign the number of days with variable or overcast cloud conditions was limited. Similar work of Weihs et al (2008) showed under partly cloudy conditions the satellite UV-values are, on average, in the order of 30% higher than the ground observations. The ratio OMI to ground UV becomes even larger for overcast conditions.…”
Section: Comparisons With Omi Overpass Datasupporting
confidence: 58%
“…Satellite ozone and UV data were exhaustively validated by means of GB measurements, regarding TOMS; (Kalliskota et al, 2000;McKenzie et al, 2001;Krotkov et al, 2001;Fioletov et al, 2002;Meloni et al, 2005;Arola et al, 2005;Kazantzidis et al, 2006) and lately OMI; Ialongo et al, 2008;Weihs et al, 2008;Kazadzis et al, 2009;Buchard et al, 2008). All these validation studies converge to the following conclusions:…”
Section: S Kazadzis Et Al: Omi Sub-pixel Uv Irradiance and Aerosol mentioning
confidence: 95%
See 2 more Smart Citations
“…In the 1970s and 1980s, surface radiation studies in Austria were focused on establishing radiation climatologies and increasing the process understanding based on the available station data (e.g., Neuwirth, 1980Neuwirth, , 1983. From the mid-1990s until today, work related to ultraviolet (UV) radiation and health risks (e.g., Blumthaler et al, 1996;Rieder et al, 2010;Weihs et al, 2008Weihs et al, , 2013, to the role of aerosols in alpine valleys (e.g., Blumthaler et al, 1997;Wuttke et al, 2012) and studies dealing with anthropogenic influences on radiative fluxes and solar energy (e.g., Weihs et al, 2015) predominated in Austria.…”
Section: Introductionmentioning
confidence: 99%